Dr. Klein's Interpretation of Leontief's System–A Rejoinder - Morishima, Michio (Review of Economic Studies, 1957)
Journal Article Dr. Klein's Interpretation of Leontief's System—A Rejoinder Get access Michio Morishima Michio Morishima Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 25, Issue 1, October 1957, Pages 59–61, https://doi.org/10.2307/2296124 Published: 01 October 1957